Synthesis of ZSM‐5 by hydrothermal method with pre‐mixing in a stirred‐tank reactor. (22nd August 2019) - Sun, Baochang; Kang, Yingying; Shi, Qin; Arowo, Moses; Luo, Yong; Chu, Guangwen; Zou, Haikui
Abstract : This work proposed a synthesis route of ZSM‐5 via the hydrothermal method with premixing in a stirred tank reactor (STR). Effects of various operating conditions, including pre‐mixing time, molar ratio of SiO2 /Al2 O3, TPAOH (organic template agents) concentration, NaCl (alkali metal cations) concentration, crystallization temperature, and crystallization reaction time, on the average particle size (PS) and particle size distribution (PSD) were investigated. It was found that the pre‐mixing time in the STR significantly affect the formation of proto‐nuclei in premixing process and crystal growth in hydrothermal reaction process, and consequently influence the PS and PSD of the prepared ZSM‐5. ZSM‐5 with good thermal stability, a PS of 380 nm, PSD of 0.17–0.9 µm, pore diameter of 2.31 nm, pore volume of 0.19 cm 3  · g −1 and specific surface area of 337.25 m 2  ·  g −1 were obtained under the optimal conditions of a crystallization reaction time of 24 h, a crystallization temperature of 130 °C, a molar ratio of SiO2 /Al2 O3 of 200, a TPAOH concentration of 3.5 mol · L −1, NaCl concentration of 0.3 mol · L −1, and a pre‐mixing time of 5 h. This work indicated that the operating conditions including premixing time have a significant effect on its PS and PSD.